Early Secondary Alveolar Bone Grafting and Facial Growth of Patients with Complete Unilateral Cleft Lip and Palate. (June 2023) - Doucet, Jean-Charles; Russell, Kathleen A.; Daskalogiannakis, John; Mercado, Ana M.; Hathaway, Ronald R.; Semb, Gunvor; Shaw, William C.; Long, Ross E.
Objective: To investigate the craniofacial growth outcomes of early secondary alveolar bone grafting(ABG) around 6 years of age. Design: Retrospective cohort study Setting: 1 North-American and 5 Northern-European cleft centers. Subjects: 33 subjects with CUCLP consecutively treated with secondary ABG around 6 years of age were compared to 105 subjects from 4 centers treated with late secondary ABG and 19 subjects from 1 center with primary ABG. Methods: Preorthodontic standardized lateral cephalometric radiographs taken after 12 years of age were traced and analyzed according to the Eurocleft Study protocol. Fourteen angular and two proportional measurements were performed. Measurement means from the Study Center(SC) were compared to 5 Northern-European centers using analysis of variance and Welch's modified t -tests, and P  < .05 was considered statistically significant. Results: For the SC, the mean age ± SD at the time of bone graft was 5.85 ± 0.71 years and the mean age at the time of the lateral cephalogram was 13.4 ± 1.8 years. The sagittal maxillary prominence of the SC was favorably comparable to the 5 Northern-European centers. The mean SNA (78.1 ± 4.3) for the SC was significantly higher compared to 4 of the 5 Northern-European centers(all P  < .05), and the mean ANB angle was comparable to 4 of the 5 centers. Similarly, the mean soft tissue ANB angle was not significantly different to the 5 centers. The soft tissue vertical proportions compared favorably to all 5 Northern-European centers(all P  < .01). Conclusions: Craniofacial growth outcomes of early secondary ABG around 6 years compare favorably to the outcomes of late secondary ABG.